The geography of the everyday : toward an understanding of the given - Sullivan, Robert E., 1952- (University of Georgia Press, 2017)
"Anthropologists, psychologists, feminists, and sociologists have long studied the 'everyday, ' the quotidian, the taken-for-granted; however, geographers have lagged behind in engaging with this slippery aspect of reality. Now, Rob Sullivan makes the case for geography as a powerful conceptual framework for seeing the everyday anew and for pushing back against its 'givenness': its capacity to so fade into the background that it controls us in dangerously unexamined ways. Drawing on a number of theorists (Foucault, Goffman, Marx, Lefebvre, Hägerstrand, and others), Sullivan unpacks the concepts and perceived realities that structure everyday life while grounding them in real-world cases, such as Nigeria's troubled oil network, the working poor in the United States, China's urban villages, and ultra-high-end housing in London and Cairo